2016
DOI: 10.1101/081745
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Functional determinants of protein assembly into homomeric complexes

Abstract: Approximately half of proteins with experimentally determined structures can interact with other copies of themselves and assemble into homomeric complexes, the overwhelming majority of which (>96%) are symmetric. Although homomerisation is often assumed to a functionally beneficial result of evolutionary selection, there has been little systematic analysis of the relationship between homomer structure and function. Here, utilizing the large numbers of structures and functional annotations now available, we ha… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 58 publications
1
30
0
Order By: Relevance
“…A thermodynamic model based on tethered dimerization revealed that the observed activity enhancement partially originates from a statistical increase in the number of active catalytic units in higher-order enzyme configurations. We envision that clustering of catalytic enzymatic subunits into higher-order complexes, either through SMOC-based assembly 4,5 , functional homotypic interactions 62,63 , or via liquid phase separation 64,65 , could represent a general mechanism for enzymatic activity enhancement or regulation in various intracellular processes.…”
Section: Resultsmentioning
confidence: 99%
“…A thermodynamic model based on tethered dimerization revealed that the observed activity enhancement partially originates from a statistical increase in the number of active catalytic units in higher-order enzyme configurations. We envision that clustering of catalytic enzymatic subunits into higher-order complexes, either through SMOC-based assembly 4,5 , functional homotypic interactions 62,63 , or via liquid phase separation 64,65 , could represent a general mechanism for enzymatic activity enhancement or regulation in various intracellular processes.…”
Section: Resultsmentioning
confidence: 99%
“…16, 2018; 2 The assembly of genetically-encoded molecules into symmetric, supramolecular materials enables complex functions in natural biosystems and would likewise prove valuable in the development of bionanotechnologies including drug delivery, energy transport, and biological information storage. [1][2][3][4][5][6][7] Repeated, symmetric interactions between molecular building blocks enable the formation of complex, defined, assemblies from a small total number of components as well as dynamic propagation of conformational change. [3][4][5][6][7][8] However, while de novo engineering of artificial symmetrical biomolecular complexes has begun to be explored, 9-15 these efforts generally rely upon precise design of molecular interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Given that both natural proteins [3][4][5][6][7][8] and synthetic colloids [18][19][20][21][22][23][24][25][26][27][28][29] have been shown to readily assemble into symmetric, higher order structures, we anticipate that our SuPrA strategy can now be generalized to create synthetic, scalable…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this analysis, we propose that, whilst the evolutionary ancient and highly conserved dimeric interface of MAT controls its primary enzymatic function and the assembly path of the tetramer, the more recent inter-dimeric interface is recruited by evolution to tune the molecular properties of the entire tetramer and tailor them to the specific needs of the organism. Finally, the existence of the homomer-level modes of regulation of stability and activity that stems from the evolutionary tinkering of the interdimeric interface also provides a clue as to why dihedral homomers exhibit a particularly strong functional enrichment in metabolic enzymes (Bergendahl and Marsh, 2017). a and b, and between chains c and d), and inter-dimeric interface between dimers ab and cd.…”
Section: Discussionmentioning
confidence: 99%